Auxetic textiles - Hu, Hong; Zhang, Minglonghai; Liu, Yanping (Woodhead Publishing, an imprint of Elsevier, 2019)
Auxetic Textiles provides a detailed introduction to the basic properties of auxetic materials and how they differ from conventional materials, particularly auxetic textiles, such as polymers, fibers, yarns, fabrics and textile composites. The book discusses the beneficial properties of auxetic structures in textiles and how to translate those benefits into actual materials development. Sections cover the deformation mechanism of textile structures to achieve auxetic behavior and the modelling and simulation of auxetic textile structures. Finally, the book provides expert insights into potential application areas. Cutting across textiles disciplines, from technical textiles and advanced composites, to fashion and design, the book is a valuable introduction to the field for newcomers, with potent insights into the potential of these materials.